Estimation of the product yield and collection efficiency of peripheral blood stem cell harvesting using peripheral blood CD34+ cells quantification / Habsah Aziz - Habsah, Aziz (2010)
Peripheral blood stem cells (PBSC) have been used for transplantation since the early 1990s. CD34+ has been used as a marker of hematopoietic stem cells to determine the optimal timing for PBSC harvesting. However, a wide ranges of CD34+ cells cut-off values from 8/ul to 66/ul have been used to initiate PBSC harvesting in autologous patients. We performed here a study to determine the peripheral blood CD34+ cells cut-off value for the prediction of stem cell yield of 2 x106 CD34+ cells/kg body weight patients, to study the correlation between peripheral blood CD34+ cells and stem cell yield, to study the correlation between the day 1 post-apheresis and day 2 pre-apheresis CD34+ count and to study the collection efficiency of the apheresis protocol used. Forty eight patients with a total of 94 PBSC harvesting procedures were analyzed. All apheresis were performed using a COBE Spectra TM Apheresis System. Pre and post apheresis peripheral blood CD34+ cells as well as the harvested CD34+ cell count were analysed using FACSCalibur flow cytometer. The CD34+ harvesting cut-off value was determined using the Receiver Operating Characteristic (ROC) curve analysis and the correlation study was done using Pearson’s Correlation Analysis. The cut-off value of  27 cells/ul has been shown to predict a stem cell yield of  2 x106 CD34+ cells/ kg body weight with a single apheresis with 95% sensitivity and 82.4% specificity. Pre-apheresis peripheral blood CD34+ cell count correlated well with the stem cell yields (r = 0.963 and p<0.001). The day 1 post-apheresis peripheral blood CD34+ cell count correlates well with day 2 pre-apheresis count (r = 0.895), and a value of ≥ 25 cells/ul and may be able to predict the day 2 stem cell yield of  2 x106 CD34+ cells/ kg body weight. The median overall collection efficiency of the stem cell harvesting protocol was 63.7%. iv In conclusion, this study has shown that PB CD34+ count of  27 cells/ul will predict the stem cell yields of  2 x106 CD34+ cells/ kg body weight, and the apheresis protocol used for peripheral blood stem cell harvesting has gave satisfactory collection efficiency.